Experiential Learning untuk Meningkatkan Kompetensi Multikultural Mahasiswa - Djamaluddin, Mawardi; Lasan, Blasius Boli; Atmoko, Adi (Jurnal Kajian Bimbingan dan Konseling, 2018)
The study aims at measuring the effectiveness of experiential learning model for improving the multicultural competence of non-Javanese students in the Malang City. The true-experiment type quantitative study is conducted by using the pretest-posttest control group design. The subjects were 20 non-Javanese students in several universities in Malang City that had low multicultural competence. The Wilcoxon Signed Rank Test was implemented in order to compare the score of the students before and after the treatment. In addition, Mann-Whitney U Test was also implemented in order to compare the level of effectiveness statistically between the control group and the experimental group after the provision of the treatment. The results of the study show that the experimental group has significant mean score of multicultural competence in comparison to the control group. The statement implies that the experiential learning model has been effective in improving the multicultural competence of non-Javanese students.